Implementation of POAC Management Function in Sustainable Tourism Development in Panglipuran Traditional Village, Bali - Fannisa Nabila Shafira; Farhati Silvia; Nayva Risalwa Wibowo; Febiola Hengrida Almayra; Ziana Zain Ramadhan (Pustaka Digital Indonesia, 2026)
This study aims to analyze the implementation of POAC (Planning, Organizing, Actuating, and Controlling) management functions in sustainable tourism management in Penglipuran Traditional Village, Bali, as well as identify challenges and opportunities for its development. This study uses a descriptive qualitative approach with a literature-based case study type. Data was obtained from scientific articles, books, and relevant documents that discuss Penglipuran Tourism Village, Tri Hita Karana, community empowerment, and sustainable tourism. Data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that the planning function is carried out through the preparation of tourism development directions based on the values of Tri Hita Karana; the organizational function is realized through the division of roles between communities, customary institutions, and tourism managers; The implementation function can be seen in the management of tourism activities that maintain customs, traditional architecture, environmental cleanliness, and bamboo forests; Meanwhile, the supervisory function is carried out through awig-awig and community social control. Nevertheless, Penglipuran Traditional Village faces challenges in the form of overtourism, environmental pressures, cultural commercialization, and economic dependence on the tourism sector. Therefore, it is necessary to strengthen customary regulations, visitor capacity management, and diversify the creative economy based on local wisdom.